2015
DOI: 10.4103/2278-330x.155691
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Cynodon dactylon L. root extract against diethyl nitrosamine induced hepatic carcinoma

Abstract: Background:Hepatocellular carcinoma is one of the most common cancers and a lethal disease. In view of the limited treatment and a grave prognosis of liver cancer, preventive control has been emphasized.Materials and Methods:The methanolic extract of roots of Cynodon dactylon was screened for its hepato-protective activity in diethyl nitrosamine (DEN) induced liver cancer in Swiss albino mice. The plant extract at a dose of 50 mg/kg was administered orally once a week, up to 30 days after DEN administration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Administration of melatonin to DEN-treated animals indicated that the indole was able to reduce hepatocarcinogenic features in HCC-bearing rats, because it ameliorated histology, and reduced changes in serum enzymes and in the expression of GST-P, a protein considered a marker of hepatocarcinogenesis[ 36 ]. These findings are in accordance with results by different authors that also used DEN as a HCC promoter and tested effects of melatonin or other antioxidants, such as resveratrol, maotai or daffron, in rats [ 24 , 37 40 ] and mice [ 41 ]. Melatonin also prevented DNA damage in DEN-treated animasl, probably due to its capacity to regulate several key genes involved in DNA repairing pathways, such as CEP152 and N4BP2L2 [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Administration of melatonin to DEN-treated animals indicated that the indole was able to reduce hepatocarcinogenic features in HCC-bearing rats, because it ameliorated histology, and reduced changes in serum enzymes and in the expression of GST-P, a protein considered a marker of hepatocarcinogenesis[ 36 ]. These findings are in accordance with results by different authors that also used DEN as a HCC promoter and tested effects of melatonin or other antioxidants, such as resveratrol, maotai or daffron, in rats [ 24 , 37 40 ] and mice [ 41 ]. Melatonin also prevented DNA damage in DEN-treated animasl, probably due to its capacity to regulate several key genes involved in DNA repairing pathways, such as CEP152 and N4BP2L2 [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, various enzymes, such as ALT, AST, LDH and CK are notably increased in human serum with liver metastases of HCC. 51 Similar observations were noted in NDEA-exposed rats and the levels were brought down to normalcy with 5-FU, 4A and 6A drug treatments; predominantly, the impact of 4A is comparable to standard 5-FU.…”
Section: Discussionsupporting
confidence: 68%
“…DEN and 2-AAF are the chemicals that cause tumours to form in the biological system. [ 23 - 24 - 25 ]. Co-administration of DEN and 2-AAF initiates hepatocarcinogenesis in rodents and causes preneoplastic initiation in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%